The effect of price and customer satisfaction on online orchid purchase decisions in Batam City - Tussi Sulistyowati; Nur Elfi Husda (Universitas Muhammadiyah Malang, 2024)
This study highlights the crucial role of price and customer satisfaction in influencing purchase decisions within the online orchid market in Batam City. Utilizing SEM-PLS analysis with 112 purposively sample respondents, the research reveals a significant impact of price on both customer satisfaction and purchase decisions. Although trust was found to have a less direct effect on purchase decisions, its role in shaping customer satisfaction underscores the complexity of consumer behavior. The study’s limitations include its focus on a specific sample from Batam City, which may limit the generalizability of the findings to other regions or markets. Future research should aim to broaden the sample size, include participants from various geographic locations, and examine additional variables that might influence consumer behavior. These insights suggest that MSMEs should prioritize optimizing pricing strategies, enhancing customer satisfaction through superior service, and tailoring marketing efforts to local market conditions. Addressing these factors will help businesses better meet customer expectations, build loyalty, and achieve sustained success in niche markets such as online orchids.